Actual versus Simulated Breast and Rectal Examinations among Recent Medical Student Graduates - Nora H. Trabulsi; Shayma M. Alotaibi; Hajar F. Alghamdi; Mohammad M. Abbas; Nouf Y. Akeel; Ali A. Samkari; Ali H. Farsi; Nadim H. Malibary; Abdulaziz M. Saleem; Mai S. Kadi; Mohammed O. Nassif (Journal of King Abdulaziz University: Medical Sciences, 2020)
Clinical skills form the core of a physician’s practice. Breast and rectal examinations help the physician to detect abnormalities that may lead to the identification of unnoticed diseases. Learning these skills with real patients can be difficult because patients can be hesitant to allow students to perform these examinations. Simulation-based teaching is a viable option for overcoming these obstacles. A cross-sectional study was performed that included interns at King Abdulaziz University. Of the 252 students who completed the questionnaire, most performed a breast examination on manikins. Among all, 206 reported that practicing on manikins prepared them to deal with real patients. More female than male students performed breast examinations on real patients. Rectal examinations were slightly less prevalent, with 223 students having performed them on manikins. Among all, 183 reported that this prepared them to deal with real patients. The most frequent barrier to performing an examination on real patients was the patient’s refusal due to religious and cultural concerns. It is of paramount importance for doctors to help students perform these examinations under supervision on real patients. This could be achieved by encouraging doctors to supervise students’ examinations more frequently and by improving students’ communication skills.